2002
DOI: 10.1038/ng838
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-associated protein 1A is a modifier of tubby hearing (moth1)

Abstract: Once a mutation in the gene tub was identified as the cause of obesity, retinal degeneration and hearing loss in tubby mice 1-2 , it became increasingly evident that the members of the tub gene family (tulps) influence maintenance and function of the neuronal cell lineage [3][4][5][6] . Suggested molecular functions of tubby-like proteins include roles in vesicular trafficking 4,7 , mediation of insulin signaling 8 and gene transcription 9,10 . The mechanisms through which tub functions in neurons, however, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 17 publications
1
72
0
Order By: Relevance
“…For instance, the dominant allele of modifier-of-tubby-hearing 1 (moth1), segregating in AKR/J, rescues hearing loss in a significant fraction of tubby homozygotes (Ikeda et al 1999). Recently, nonsynonymous sequence polymorphisms in the microtubule-associated protein 1a gene (Mtap1a) were associated with moth1 supporting previous evidence that tubby plays a role at synapses (Ikeda et al 2002). The molecular mechanisms underlying genetic modification are currently not well understood, but further studies will undoubtedly show how modifiers exert their effects on the mutant allele.…”
Section: Introductionmentioning
confidence: 61%
“…For instance, the dominant allele of modifier-of-tubby-hearing 1 (moth1), segregating in AKR/J, rescues hearing loss in a significant fraction of tubby homozygotes (Ikeda et al 1999). Recently, nonsynonymous sequence polymorphisms in the microtubule-associated protein 1a gene (Mtap1a) were associated with moth1 supporting previous evidence that tubby plays a role at synapses (Ikeda et al 2002). The molecular mechanisms underlying genetic modification are currently not well understood, but further studies will undoubtedly show how modifiers exert their effects on the mutant allele.…”
Section: Introductionmentioning
confidence: 61%
“…Moreover, the measurement of ABR threshold has proven essential in identifying modifier genes (Ikeda et al, 2002;Johnson and Zheng, 2002;Johnson et al, 2000Johnson et al, , 2001Noben-Trauth et al, 1997Zheng and Johnson, 2001). However, previous studies have shown that, while some hearing impairments were characterized by significant changes in all ABR parameters such as the threshold, amplitude, and latency, others were associated with the abnormalities in the amplitude and latency but not the threshold (Evans et al, 1983;Fujiyoshi et al, 1994;Kanzaki et al, 1985).…”
Section: Introductionmentioning
confidence: 89%
“…The successful use of ABR threshold for assessment of the hearing sensitivity of mice has lead to strain characterization , gene localization (Galambos and Hecox, 1978;Henry, 2004;Hirose and Liberman, 2003;Huang and Buchwald, 1978;Hunter and Willott, 1987;Ikeda et al, 2002;Ingham et al, 1998;Jimenez et al, 1999;Johnson et al, 2001), and gene identification (Ikeda et al, 2002;Johnson et al, 2000Johnson et al, , 2001Johnson et al, , 2003 since 1997. Moreover, the measurement of ABR threshold has proven essential in identifying modifier genes (Ikeda et al, 2002;Johnson and Zheng, 2002;Johnson et al, 2000Johnson et al, , 2001Noben-Trauth et al, 1997Zheng and Johnson, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…MAP1A interacts with actin and postsynaptic components like PSD93/PSD95, and anchors NMDA receptors to the cytoskeleton, supporting their transport along the dendrites (Brenman et al 1998;Pedrotti et al 1994b;Reese et al 2007;Takei et al 2015). Loss of the MAP1A-PSD95 interaction has been associated with hearing loss, due to defects in synaptic function (Ikeda et al 2002). MAP1A also ⁄ ä has a presynaptic function.…”
Section: Map1 Family Member Map1amentioning
confidence: 99%